’Gas’ a Popular Term but it may not be Gastric Ulcer - Islam, MM Shahin-Ul (Faridpur Medical College Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20279 Faridpur Med. Coll. J. 2013;8(2): 48